Targeting Vascular Endothelial Growth Factor in Oesophagogastric Cancer: A Review of Progress to Date and Immunotherapy Combination Strategies - Butters, Oliver; Young, Kate; Cunningham, David; Chau, Ian; Starling, Naureen (Frontiers in Oncology, 2019)
In 2014, the survival benefits seen in REGARD and RAINBOW studies led the way for the regulatory approval of ramucirumab in the second line setting in oesophagogastric (OG) cancer. Trials of other drugs targeting the vascular endothelial growth factor (VEGF) pathway have met with mixed results but this remains an important pathway for evaluation in OG cancer. Perhaps the most interesting ongoing trials are those which target VEGF in combination with immunotherapy, which have a sound scientific rationale. Given the emerging role of immunotherapy in OG cancer, this is an important area of innovation. This review aims to outline targeting VEGF in OG cancer, the rationale behind the continued interest in this mechanism and possible future directions in combination with immunotherapy.